Structure and trajectory optimization for redundant manipulators - Pires, E. J. Solteiro (2019)
This paper proposes a genetic algorithm to generate a robot structure and the required manipulating trajectories. The objective is to minimize the space/time ripple in the trajectory without colliding with any obstacles in the workspace, while optimizing the mechanical structure.